Thermally induced fracture and thermomechanical properties of NI-MN-GA-FSMA single crystals - Xiong, Feng (2008)
In this research, thermomechanical behavior and thermally induced fracture of single crystal Ni-Mn-Ga FSMAs were investigated. Results show that 1. Ni-Mn-Ga FSMAs exhibited two way memory effect during thermal cycling; however, the stability is very sensitive to the temperature rate and external load. 2. The crack propagation behavior is strongly related to the forward transformation and the martensitic twin structure. Thermomechanical fatigue cracks in Ni-Mn-Ga FSMAs prefer to propagate along the twin boundaries as well as twin-twin intersections through multiple propagation modes. 3. Theoretical analysis on the thermally induced fracture behavior of Ni-Mn-Ga FSMA shows that the primary reason for the thermally induced fracture in Ni-Mn-Ga FSMAs is the increase in the crack tip stress intensity factor (SIF) due to stress redistribution around the crack tip as a result of stress-induced martensitic (SIM) transformation. With lowering the temperature to approach to the martensite start temperature, the crack tip SIF of Ni-Mn-Ga FSMA increases significantly, which is responsible for its brittleness under thermal cycling and is strongly related to the yield stress, temperature dependence of the critical stress for SIM transformation and transformation interval.